2022
DOI: 10.3389/fneur.2022.838746
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Factors Associated With Sepsis-Associated Encephalopathy in Children: Retrospective Single-Center Clinical Study

Abstract: BackgroundSepsis-associated encephalopathy (SAE) is a common complication in septic patients with a higher ICU and hospital mortality in adults and poorer long-term outcomes. Clinical presentation may range from mild confusion to convulsions and deep coma; however, little is known about SAE in children. We aimed to retrospectively analyze the data for children with sepsis, to illustrate the epidemiology, performance, and adverse outcome, and to evaluate the association between risk factors and SAE in children.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…A previous study among adult patients with sepsis found that acute renal failure, hypoglycemia, hypercapnia, hypernatremia, and S. aureus infection were independent predictors of SAE [ 19 ], and the different results from our study demonstrated a difference between adult and pediatric patients. Another retrospective single-center study of 210 pediatric patients with sepsis showed that procalcitonin, Ca 2+ , septic shock, pediatric logistic organ dysfunction score 2 (PELOD-2), and midazolam were independent risk factors for SAE; however, no comprehensive predictive model has been developed [ 20 ]. Moreover, our study showed that SAE was associated with higher in-hospital mortality and higher use of ICU resources, confirming the early predictive value of SAE at PICU admission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study among adult patients with sepsis found that acute renal failure, hypoglycemia, hypercapnia, hypernatremia, and S. aureus infection were independent predictors of SAE [ 19 ], and the different results from our study demonstrated a difference between adult and pediatric patients. Another retrospective single-center study of 210 pediatric patients with sepsis showed that procalcitonin, Ca 2+ , septic shock, pediatric logistic organ dysfunction score 2 (PELOD-2), and midazolam were independent risk factors for SAE; however, no comprehensive predictive model has been developed [ 20 ]. Moreover, our study showed that SAE was associated with higher in-hospital mortality and higher use of ICU resources, confirming the early predictive value of SAE at PICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most commonly used indicators of the endogenous coagulation system in clinical practice, APTT was previously shown to be significantly increased in children with SAE compared to those without [ 20 ]. Similarly, in the present study, APTT was significantly associated with the occurrence of SAE ( P < 0.001) and was included in the prediction nomogram because of its strong influence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical pathophysiology of the progression of brain dysfunction is likely multifactorial and associated with more severe illness characterized by early neurologic dysfunction (2) and persistent hypoxemia (3). This neurologic entity goes by a variety of terms including sepsis-associated encephalopathy, sepsis-induced brain dysfunction, or sepsis-associated delirium (4), the cause of which may be as widespread as direct infection, structural brain lesions, metabolic and biochemical derangement, pharmacologic exposures, and inflammation (4)(5)(6).…”
mentioning
confidence: 99%